Pemetaan Level Literasi Kimia Peserta Didik Kelas XI MIPA di SMAN 1 Lubuk Basung pada Materi Termokimia dengan Model Rasch - Novia Anggraini; Eka Yusmaita (Universitas Negeri Padang, 2021)
This study aims to analyse the mapping of chemical literacy levels of students in class XI MIPA at SMAN 1 Lubuk Basung on thermochemical material using the Rasch model according to the scientific literacy framework adapted by Shwartz. This study is a quantitative study using a sample of 50 students of class XI MIPA. The data is obtained from a chemical literacy test, then the data is analysed using the Rasch model. The results showed that students with the highest abilities have the right answers but have not been able to define the concepts and understanding is limited, meanwhile students with the lowest ability have wrong or blank answers. Thus, it was concluded, students with the highest abilities have a functional scientific literacy level on difficult items and students with the lowest abilities have a scientific literacy level.